Movement and Language Development as an Early Childhood Twin Strategy: A Systematic Review - Manuela Valentini; Cristina Bernardini; Alessandro Beretta; Gaetano Raiola (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
In this review, a critical reading of the literary and scientifi c production focused on the themes of the body, movement and language learning was carried out, with particular consideration given to alternative teaching methods that use movement to favour the cognitive process. After searching the databases of Pub Med, PsycInfo, Sport Discus, Psyc Articles and Eric electronic, the choice was narrowed down to 8 international scientifi c studies with publication dates ranging between the years 1999 and 2017 concerning pre-school subjects between 2 and 5 years of age, excluding those regarding other target users and/or particular characteristics such as pathologies, obesity, and nutrition. All of these studies analysed the benefi ts of motor activity on language, communication, learning and academic performance. Of the 7 fi ltered studies, 4 examine the specifi c relationship between motor activity and language, while the other 3 between language and general academic performance. Through the analysis of the fi ltered reports and some of the bibliographical references used, we conclude that motor activity positively infl uences language, attention and concentration of the pupils in this age range, with eff ects on academic performance. Furthermore, it also improves motor skills as a result of decreased sedentary behaviour.